(untitled) (Swiss Medical Weekly, 2025)
STUDY AIMS: Although costs for inpatient palliative care have been widely studied, heterogeneity of patient needs in specialist palliative care challenges health scientists. A framework reflecting various treatment goals in daily clinical practice may help cluster patients with different care needs reasonably and account for such diversity of costs. The aim of this study was to show whether the care type framework reflects associated costs for different care needs in patients receiving specialist palliative care in a Swiss university hospital. METHODS: We performed a retrospective, observational analysis of hospital costs using administrative data from a Swiss university hospital of all specialist palliative care inpatients in the period 2016–2022. Patients were classified at admission into four different palliative care types reflecting treatment goals: care type 1: extensive palliative care needs (biopsychosocial-spiritual), goal = stabilisation and setting of realistic goals; care type 2: mobility evaluation and training, goal = return home; care type 3: focused symptom management, goal = symptom relief; care type 4: care for dying patients, goal = dying with dignity. We used a generalised linear model assuming gamma-distributed errors and with a logarithmic link function, adjusted by inverse probability weighting to adjust for differences in patient characteristics. We hypothesised that patients – classified into one of four care types based on treatment goals – differed substantially by cost, with care type 1 being most expensive. RESULTS: Of 1099 included patients, overall unadjusted median costs per patient during specialist palliative care treatment were CHF 20,253 (interquartile range [IQR] 12,327–30,104). Median costs (% of total patients; median length of stay) by care type were: CHF 23,999 for care type 1 (44%; 13 days); CHF 21,598 for care type 2 (9%; 14 days); CHF 17,946 for care type 3 (24%; 12 days); and CHF 14,997 for care type 4 (23%; 8 days). Patients showed clearly different adjusted overall costs and adjusted daily costs by care type. Overall potential mean costs were the lowest for care type 4 (CHF 21,908) and clearly different (-15%) from the most expensive care type 1 (CHF 25,827). In contrast, potential mean daily adjusted costs were the most expensive for care type 4 (CHF 2361). Most daily costs for care type 4 (88%) belonged to the cost category “staff costs” (CHF 2070) of which 59% (CHF 1229) were nursing costs. CONCLUSION: Based on distinct treatment goals, care types provide an important yet – until now – missing explanatory framework for clustering hospital costs of specialist palliative care. Patients hospitalised in specialist palliative care units clearly differ regarding costs and cost categories, depending on care type.